Strategi Pemasaran Digital melalui Shopee dalam Pengembangan Usaha Hijab Lokal: Studi Kualitatif pada Voilaya Hijab - Salsabila Dwi Anggraini; Tri Retno Tunggal Dewi; Kristanti Subbagijo; Khofifah Azizah Masfufah; Dhevy Widyawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Consumer spending patterns have shifted as a result of advances in digital technology and the increasing use of the internet, particularly in online shopping activities. This phenomenon has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt e-commerce platforms as their primary marketing strategy. This study employs a qualitative analysis of Voilaya Hijab to examine Shopee’s digital marketing techniques in developing a local hijab business. Data were collected through in-depth interviews, non-participant observation, and documentation as part of this descriptive qualitative study. The findings indicate that the utilization of Shopee features such as Shopee Ads, Shopee Live, flash sales, discount vouchers, and enhanced visual product content significantly increases sales, expands market reach, and strengthens brand awareness. In addition to serving as a practical reference for hijab-based MSMEs, this study is expected to contribute academically to the advancement of digital marketing research.